The tumor therapeutic potential of long non-coding RNA delivery and targeting - Shuo Han; Xinru Chen; Leaf Huang (Elsevier, 2023)
Long non-coding RNAs (lncRNAs) is a type of RNA over 200 nt long without any protein coding ability, which has been investigated relating to crucial biological function in cells. There are many key lncRNAs in tumor/normal cells that serve as a biological marker or a new target for tumor treatment. However, compared to some small non-coding RNA, lncRNA-based drugs are limited in clinical application. Different from other non-coding RNA, like microRNAs, most lncRNAs have a high molecular weight and conserved secondary structure, making the delivery of lncRNAs more complex than the small non-coding RNAs. Considering that lncRNAs constitute the most abundant part of the mammalian genome, it is critical to further explore lncRNA delivery and the subsequent functional studies for potential clinical application. In this review, we will discuss the function and mechanism of lncRNAs in diseases, especially cancer, and different approaches for lncRNA transfection using multiple biomaterials.